Astroglial gap junctions strengthen hippocampal network activity by sustaining afterhyperpolarization via KCNQ channels - Dossi, Elena; Zonca, Lou; Pivonkova, Helena; Milior, Giampaolo; Moulard, Julien; Vargova, Lydia; Chever, Oana; Holcman, David; Rouach, Nathalie (Cell reports, 2024)
Throughout the brain, astrocytes form networks mediated by gap junction channels that promote the activity of neuronal ensembles. Although their inputs on neuronal information processing are well established, how molecular gap junction channels shape neuronal network patterns remains unclear. Here, using astroglial connexin-deficient mice, in which astrocytes are disconnected and neuronal bursting patterns are abnormal, we show that astrocyte networks strengthen bursting activity via dynamic regulation of extracellular potassium levels, independently of glutamate homeostasis or metabolic support. Using a facilitation-depression model, we identify neuronal afterhyperpolarization as the key parameter underlying bursting pattern regulation by extracellular potassium in mice with disconnected astrocytes. We confirm this prediction experimentally and reveal that astroglial network control of extracellular potassium sustains neuronal afterhyperpolarization via KCNQ voltage-gated K+ channels. Altogether, these data delineate how astroglial gap junctions mechanistically strengthen neuronal population bursts and point to approaches for controlling aberrant activity in neurological diseases.
Keywords: Neurons; connexins; Potassium; KCNQ channels; networks; akční potenciály; konexiny; mathematical modeling; Action Potentials; draslík; KCNQ Potassium Channels; hipokampus; afterhyperpolarization; potassium; draslíkové kanály KCNQ; Astrocytes; myši inbrední C57BL; mužské pohlaví; Mice; gap junctions; myši knockoutované; astrocyty; CP: Neuroscience; ženské pohlaví; Nerve Net; zvířata; nervová síť; neurony; Mice, Knockout; myši; mezerový spoj; Gap Junctions; Connexins; astrocytes; Female; Mice, Inbred C57BL; bursting; Male; Hippocampus; Animals